The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1984
DOI: 10.1002/cjce.5450620124
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature and time on interfacial tension behavior between heavy oils and alkaline solutions

Abstract: Heavy oils contain significantly more acidic components than conventional crude oils. Upon contact with aqueous alkaline solutions, water‐soluble surfactants are formed in‐situ at the interface. These surfactants have the ability to reduce the oil/water interfacial tension to ultra‐low values. This work studies the significant effects of time and temperature on the interfacial tension between alkaline solutions and two Canadian heavy oils (Lloydminster and Cold Lake). The results obtained indicate that the tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

1987
1987
2001
2001

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Equation [3], which assumes that the double-layer potential remains constant during the approach, provides a good estimate of the repulsive potential energy. Overbeek (28) has shown that the linear approximation assumed by Hogg et al (27) is remarkably good, even at a surface potential of 100 mV.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 3 more Smart Citations
“…Equation [3], which assumes that the double-layer potential remains constant during the approach, provides a good estimate of the repulsive potential energy. Overbeek (28) has shown that the linear approximation assumed by Hogg et al (27) is remarkably good, even at a surface potential of 100 mV.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…[3], it is necessary to determine the electrostatic potential ψ s and the Debye parameter κ. Several investigators (29,30) have suggested that the zeta potential (ζ ), determined by electrophoretic measurements, is approximately equal to the interfacial potential, ψ s .…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…When these surface active anions accumulate sufficiently at the oil/ water interface, the IFT may be drastically lowered. Several researchers (Jennings, 1975;McCaffery, 1976;Trujillo, 1983;Babu et al, 1984) have observed the dynamic nature of the IFT which arises in caustic-acidic crude systems. The IFT has also been shown to vary with crude oil type, reservoir salinity, and the alkalinity of the floodwater.…”
Section: Introductionmentioning
confidence: 99%